2017
DOI: 10.19052/ed.3649
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes del precio de la vivienda en Bucaramanga

Abstract: El objetivo del artículo fue analizar los cambios en los determinantes del precio de la vivienda en Bucaramanga, en 2005 y 2012, luego de la implementación del sistema de transporte público Metrolínea. Para el análisis, se utilizó el método de precios hedónicos, que explica cómo el conjunto de características convencionales y atributos del entorno de las viviendas influyen en la disposición a pagar de los consumidores. Los resultados sugieren que las características del inmueble y los atributos convencionales,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In terms of the overall fit, the model is acceptable considering that all the variables introduced presented levels of statistical significance of 5% and according to the R square in the Table 2, the model manages to explain 49.7% total and 44.7% intra groups. These R-square values are when compared to other related works in the literature are 42% for Rodriguez et al (2018) and 74% for Peña et al (2004). These papers find that these indicator levels are the result of the lack of explanatory variables within the proposed model.…”
Section: Characterization Of Housing Ownership In Colombiasupporting
confidence: 54%
See 1 more Smart Citation
“…In terms of the overall fit, the model is acceptable considering that all the variables introduced presented levels of statistical significance of 5% and according to the R square in the Table 2, the model manages to explain 49.7% total and 44.7% intra groups. These R-square values are when compared to other related works in the literature are 42% for Rodriguez et al (2018) and 74% for Peña et al (2004). These papers find that these indicator levels are the result of the lack of explanatory variables within the proposed model.…”
Section: Characterization Of Housing Ownership In Colombiasupporting
confidence: 54%
“…Peña et al (2004) make a compilation of these factors and state that among the factors involved in the evaluation of housing prices are those on the demand and supply side (Table 1). On the housing price determinants in Spain, in order of relevance are the consumer price index (CPI), construction costs, gross domestic product (GDP) per capita, the price of rents, the volume of available credit, the reference interest rate of the mortgage market, completed free housing and the population between 25 and 34 years of age (Rodriguez et al, 2018). Peña et al (2004) Several authors have identified the expansion of the real estate supply as fundamental to explaining the growth of housing prices.…”
Section: Literature Reviewmentioning
confidence: 99%